Household Spending, Social Media Addiction, and Its Impact on Muslim Family Ties - Hari Candra; Helmalia Helmalia (Share: Jurnal Ekonomi dan Keuangan Islam, 2022)
Few are aware that spending more time on social media within the home and allocating domestic work can disrupt the household's economic equilibrium. Currently, the modern way of life has eroded the values of Muslim homes. On the basis of Islamic values, Muslim household ties reflect an attitude that balances the satisfaction of needs with the allocation of time for domestic work. This study examines the relationship between the household's social media addiction, household spending, and its impact on family ties in the West Sumatra Province of Indonesia. This study employs a relational survey model and quota sampling to collect data from 250 households in the ten cities/districts of West Sumatra Province with the most significant internet usage in 2020. Various statistical analysis methods, including descriptive statistics and moderating regression analysis using ordinary least squares (OLS), are utilized for modeling throughout the entire study. The empirical findings indicate that household spending has a significant negative impact on family ties, with a coefficient of 2.00, and that social media addiction among both parents and adolescents has a relatively significant negative impact on family ties, with coefficients of 0.0011 and 0.0082, respectively. In addition, this phenomenon has not occurred across all categories of household spending, nor has marital status moderated the relationship between household spending, social media addiction, and family ties. At the same time, adolescents from divorced homes are susceptible to social media addiction.======================================================================================================== ABSTRAK – Pengeluaran Rumah Tangga, Kecanduan Media Sosial, dan Dampaknya terhadap Ikatan Keluarga Muslim. Tidak banyak yang menyadari bahwa menghabiskan lebih banyak waktu dengan media sosial di dalam rumah tangga dan mengalokasikan pekerjaan rumah tangga dapat mempengaruhi keseimbangan umum dalam ekonomi rumah tangga. Gaya hidup modern saat ini telah mengikis nilai-nilai rumah tangga Muslim. Ikatan rumah tangga Muslim merupakan sikap harmonisasi pemenuhan kebutuhan dan alokasi waktu pekerjaan rumah tangga berdasarkan landasan nilai-nilai Islam. Penelitian ini mengeksplorasi fenomena kausal kecanduan media sosial rumah tangga, pengeluaran rumah tangga, dan dampaknya terhadap ikatan keluarga di Provinsi Sumatera Barat, Indonesia. Penelitian ini menggunakan model survei relasional, dengan teknik pengambilan sampel kuota 250 rumah tangga, dari sepuluh wilayah Kota/Kabupaten di Provinsi Sumatera Barat, dengan penggunaan internet paling tinggi pada tahun 2020. Berbagai metode analisis statistik digunakan, antara lain statistik deskriptif dan analisis regresi moderasi Ordinary Least Square (OLS), untuk pemodelan selama penelitian. Temuan empiris menunjukkan bahwa pengeluaran rumah tangga berpengaruh negatif signifikan terhadap ikatan keluarga, koefisien= 2,00, dan kecanduan media sosial antara orang tua dan remaja memiliki pengaruh negatif signifikan relatif 0,0011 dan 0,0082 terhadap ikatan keluarga. Selain itu, fenomena ini belum terjadi pada semua kategori pengeluaran rumah tangga, dan status perkawinan belum memoderasi pengeluaran rumah tangga dan interaksi kecanduan media sosial pada ikatan keluarga. Pada saat yang sama, remaja di rumah tangga yang bercerai rentan terhadap paparan kecanduan media sosial.